Avaliação da corrosão causada pelo uso do biogás in natura em elementos estruturais de aço carbono de caldeiras geradoras de vapor - Fontenelle, Marcellus Tibúrcio (2015)
Biogas is a product of residual biomass from agriculture, which can increase the value to the end product of this activity, being used as a heat source in steam boilers, in small slaughterhouses or micro-plants of milk. The presence of hydrogen sulfide in biogas in natura composition causes an accelerated corrosion of the structural elements of these boilers, reducing its lifespan and compromising the safety of the workers close to it. This study evaluates the corrosion process caused by the presence of hydrogen sulfide in biogas in natura in steels commonly used in the construction of steam generating boilers, simulating the conditions close to those encountered in the application of these materials, exposing specimens directly to the biogas in natura, flaming combustion and also to the gases from the combustion of this biogas, in the chimney. After three different periods of exposure, the samples were evaluated for weight loss, establishing a correlation between the time of exposure and the loss of mass by a corrosion rate. After 314 hours of exposure under the specified conditions, the corroded surfaces of ASTM A178 and ASTM A516 steel were analyzed, by optical microscopy, scanning electron microscopy, X-ray diffraction and surface hardness, observing that the corrosion process which were submitted does not cause significant changes in the crystalline structure of the materials and that the corrosion of the materials exposed directly to the flame reduces the surface hardness of these materials where we saw the presence of cementite layer. The determination of corrosion rates for each test condition and each test material can be used as a parameter for determining the minimum allowance for mechanical stability, used as a factor "C" in calculating the minimum required thickness of the structural elements (cylindrical hull, mirrors and tubes) of the steam boilers, determined by the ASME Code, section I. Corrosion rates are not constant and may have a tendency to reduce over long exposure time, and are strongly influenced by thermal stress, due to the amount of heating and cooling cycles applied to the material exposed directly to the combustion's flame of biogas.